Prolonged skin allograft survival by rM180 amelogenin in a murine skin transplantation model - Shida, Miyu; Sanui, Terukazu; Yotsumoto, Karen; Li, Jinfeng; Ahmad, Mwannes; Xiao, Meng; Wang, Ziyu; Hayashi, Chikako; Nishimura, Yuki; Shinjo, Takanori; Taketomi, Takaharu; Fukuda, Takao; et al. (Frontiers in Immunology, 2025)
IntroductionAmelogenin, used as a periodontal tissue regeneration material, promotes healing after periodontal surgery. A previous study has demonstrated that amelogenin is taken up by macrophages into the nucleus and inhibits major histocompatibility class II (MHC II) expression at the transcriptional level, thereby suppressing subsequent T cell activation. Therefore, in this study, we focused on the suppressive effect of amelogenin on MHC II expression and examined the effect of amelogenin on graft rejection following allogeneic skin transplantation in mice with different MHC II haplotype antigens.Methods and resultsSkin grafts were treated with recombinant murine amelogenin (rM180) and transplanted into recipient mice. The rM180-treated group showed a significant increase in graft survival for up to 5.5 days and a lower necrotic score than the control group. Inflammatory cell infiltration and MHC II+ cells were significantly lower in the rM180 group. Furthermore, serum interferon-γ, interleukin-2, and interleukin-17A levels, splenic T-helper type 1 cells and helper type 17/regulatory T cells balance were reduced in the rM180 group. RNA sequencing analysis suggested "negative regulation of immune response" and "regeneration of myocytes and myofibrils" by amelogenin treatment. Among the upregulated genes in the rM180 group, “POU domain class 2 transcription factor 2,” “lipocalin 2,” and “chitinase-like 4” were ranked high. Additionally, the ratio of M2 macrophages significantly increased in rM180-treated grafts.DiscussionThese results may suggest that amelogenin can be a safe immunosuppressant or therapeutic agent against autoimmune diseases without inducing unfavorable side effects.